Navigating the digital shift: a service blueprint for coopetition technology-enabled networks - Agostinho da Silva; Antonio J. Marques Cardoso (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
This study addresses the gap in applying traditional service blueprint methodologies to technology-enabled coopetition networks characterized by simultaneous collaboration and competition among actors. Leveraging service science insights, it proposes an enhanced service blueprint framework designed for the complexities of digital coopetition. This framework introduces the cyber. Frontstage lane, physical backstage lane, and support stage lane aim to provide a holistic view of interactions, value co-creation processes, and resource allocations. Empirical validation within the Portuguese stone sector-a key player in the national economy-demonstrates the framework’s effectiveness in identifying network dysfunctions and its ease of use by industry professionals. Feedback confirms its relevance in capturing today’s coopetition environments’ multifaceted engagements and digital nuances. The study emphasizes adapting service blueprint methodology to better manage and innovate service processes in digital ecosystems. Future research should extend this framework’s application across various sectors and explore the integration of emerging technologies to optimize service delivery and value co-creation.